ANTİFUNGALLERİN SİSTEMİK MANTAR İNFEKSİYONLARINDA KULLANIMI VE DUYARLILIK DENEYLERİ: GENEL YÖNLENDİRME - YÜCEL, Ayhan; KANTARCIOĞLU, A. Serda (Cerrahpaşa Medical Journal, 2014)
Background.- This paper outlines major distinctive features of conventional antifungal agents and their common practice, and also reviews various reports related to systemic antifungal prophylaxis and therapy administrations. Furthermore, general therapeutic approaches in some special situations such as certain types of candidiasis, aspergillosis, cryptococcosis, pregnancy, and nosocomial mycoses are summarized. The significance of susceptibility tests in antifungal therapy is discussed.